Glutathione: A Key Regulator of Extracellular Matrix and Cell Death in Intervertebral Disc Degeneration - Fudong Li; Shaofei Li; Yangyang Shi; Feng Lin; Lining Rui; Jiangang Shi; Kaiqiang Sun (Hindawi Limited, 2024)
Intervertebral disc degeneration (IVDD) is a degenerative disease accompanied by the loss of nucleus pulposus cells and the degradation of extracellular matrix (ECM), which tends to be associated with lower back pain. The ECM and various types of cell death in IVDD are regulated by multiple factors, such as inflammatory responses and oxidative stress. The glutathione (GSH) redox system is the most important antioxidant defense system in cells. GSH is one of the most abundant thiol antioxidants in mammalian cells, which functions directly and indirectly by scavenging peroxides through the GSH redox system. In these reactions, GSH is oxidized by electrophilic substances, such as reactive oxygen species and free radicals, to form glutathione disulfide to exert antioxidative effects. It has been reported that GSH can protect cells against the damage of oxidative stress and various pathophysiological stimulus that can lead to different types of cell death. In addition, it was reported that the level of GSH widely participates in apoptosis, autophagy, ferroptosis, and oxidative stress in many diseases including osteoarthritis and IVDD. Therefore, we summarized the effects of GSH on ECM metabolism and cells' functions during IVDD. In addition, we summarized the regulatory effects of small molecule compounds on GSH to explore potential ways to regulate the level of GSH. Better understanding the underlying role of GSH in regulating IVDD will facilitate the goal of preventing and retarding the progress of IVDD in the future.